2013
DOI: 10.1159/000350933
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia Areata: Infiltration of Th17 Cells in the Dermis, Particularly around Hair Follicles

Abstract: Background: The precise pathogenesis of alopecia areata remains unknown, although this disease seems to be triggered by helper T cell infiltration in hair follicles. Recent studies of psoriasis and vitiligo have demonstrated the involvement of Th17 cells. Psoriasis and vitiligo occasionally develop concomitantly or inversely in patients with alopecia areata. Objective: The aim of this study was to determine whether Th17 cells are present in the affected lesions of alopecia areata. Methods: We performed immunof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 19 publications
2
63
0
1
Order By: Relevance
“…Serum cytokine levels of IL-17A are significantly increased, and TGFβ1 is significantly decreased, in patients with AA compared with controls [99]. In AA lesions, infiltration of CD4 + IL-17A + T H cells have been found in the dermis, particularly around hair follicles [100] [101]. Recently, a decrease in the number of skin infiltrating IL-17 + T cells was observed after topical immunotherapy with squaric acid dibutylester (SADBE) [102].…”
Section: Th17 Cells May Contribute To Alopecia Areata Developmentmentioning
confidence: 99%
“…Serum cytokine levels of IL-17A are significantly increased, and TGFβ1 is significantly decreased, in patients with AA compared with controls [99]. In AA lesions, infiltration of CD4 + IL-17A + T H cells have been found in the dermis, particularly around hair follicles [100] [101]. Recently, a decrease in the number of skin infiltrating IL-17 + T cells was observed after topical immunotherapy with squaric acid dibutylester (SADBE) [102].…”
Section: Th17 Cells May Contribute To Alopecia Areata Developmentmentioning
confidence: 99%
“…Tanemura et al found the infiltration of CD4(+)IL-17A(+) Th17 cells in the dermis, particularly around hair follicles, in all 4 cases in their study [98].…”
Section: Secukinumabmentioning
confidence: 57%
“…Evidence exists that the T-helper (Th)17 cell subset is a major pathogenic protagonist in many autoimmune diseases, 1 and recent data suggest a direct contribution of interleukin (IL)-17 in the development of AA. 2,3 In this study, we investigated the characteristics of the T-cell infiltrate in AA skin biopsies from five patients undergoing SAD-BE immunotherapy and we disclosed whether changes in the infiltrating T-cell subsets, in particular Th17 cells, may correlate with the clinical response to the SADBE immunotherapy.…”
Section: Conflict Of Interest: None Declaredmentioning
confidence: 99%
“…Evidence exists that the T-helper (Th)17 cell subset is a major pathogenic protagonist in many autoimmune diseases, 1 and recent data suggest a direct contribution of interleukin (IL)-17 in the development of AA. 2,3 In this study, we investigated the characteristics of the T-cell infiltrate in AA skin biopsies from five patients undergoing SAD-BE immunotherapy and we disclosed whether changes in the infiltrating T-cell subsets, in particular Th17 cells, may correlate with the clinical response to the SADBE immunotherapy.Following written informed consent, we collected 4-mm punch skin biopsies from five patients (under institutional approval and in adherence with the principles of the Declaration of Helsinki) before the initiation of the therapy (T0) and at month 3 (T3) of treatment with SADBE for isolation of infiltrating lymphocytes (Table S1). One of the five biopsies was also analyzed for immunohistochemistry study.…”
mentioning
confidence: 99%
See 1 more Smart Citation